Coitus-Free Sexual Transmission of Zika Virus in a Mouse Model. Issue 1 (December 2018) - Clancy, Chad; Wettere, Arnaud; Morrey, John; Julander, Justin
Abstract Zika virus (ZIKV) is an arboviral infection that may be sexually transmitted. The present study aims to determine if accessory sex glands are a potential source of infectious virus and important in sexual transmission. Male interferon type I receptor knockout (Ifnar −/− ) mice were challenged subcutaneously with a Puerto Rican ZIKV isolate. Reproductive tissues were harvested seven days after viral challenge and artificial insemination fluid derived from epididymis or homogenized accessory sex glands (seminal plasma) was obtained. Naïve interferon type I and II receptor knockout (AG129) females were pre-treated with progesterone, and inoculated intravaginally with either epididymal flush or seminal plasma from ZIKV-infected males. ZIKV RNA was demonstrated in the artificial insemination fluid and ZIKV antigen was detected in epididymal epithelial cells but not within seminiferous tubules at the time of artificial insemination fluid collection. Peripheral viremia, demonstrated by ZIKV RNA in whole blood samples of females from each challenge group was observed. Infectious virus was present in both epididymal fluid and seminal plasma. These studies provide evidence of passage of virus from epididymal flush and seminal plasma to naïve females via artificial insemination and provides a model for the study of sexual transmission of ZIKV.